Respostas

2014-08-02T17:11:31-03:00
A) (y+3z+2x)²= (y+3z+2x)(y+3z+2x)
=y²+3zy+2xy+3zy+9z²+6xz+2xy+6xz+4x²
=y²+6zy+4xy+12xz+4x²

b)(3x-4)²=(3x-4)(3x-4)
=9x²-12x-12x+16
9x²-24x+16

c)(x+9)²=(x+9)(x+9)
=x²+9x+9x+81
x²+18x+81
1 5 1
  • Usuário do Brainly
2014-08-03T01:55:34-03:00
(y+3z+2x)²=y²+9z²+4x²+6yz+4xy+12xz
quadrado 1°=y²
+quadrado do 2°=9z²
+quadrado do 3°=4x²
+2 vezes o 1° vezes o 2°=2.y.3z=6yz
+2 vezes o 1° vezes o 3°=2.y.2x=4xy
+2 vezes o 2° vezes o 3°=2.3z.2x=12xz

(3x-4)²=9x²-24x+16

quadrado do 1°=(3x)²=9x²
-2 vezes o 1° vezes o 2°=2.3x.4=-24x
+quadrado do 2°=4²=16

(x+9)²=x²+18x+81

quadrado do 1°=x²
+2 vezes o 1° vezes o 2°=2.x.9=18x
+ quadrado do 2°=9²=81